Exploring Reciprocal Teaching Method on EFL Learners’ Reading Comprehension - Ahmad Ridho Rojabi (Universitas Hamzanwadi, 2021)
This research was carried out as the learning activities in the reading classroom were not yet effective. As a result, the student's ability to comprehend reading texts was poor. This study aims to improve the EFL students’ reading comprehension by implementing the Reciprocal Teaching Method (RTM), especially in comprehending IELTS reading texts. Classroom action research was conducted by following four stages; planning, implementing, observing, and reflecting the actions. The Reciprocal Teaching Method (RTM) consists of four stages; predicting, questioning, clarifying, and summarizing to engage the learners in group-work activities, boost motivation, as well as enhance their comprehension. 28 learners from the English department who enrolled in the Reading course were selected as participants. Data were gathered through observations, tests, interviews, as well as document reviews. The results revealed that the Reciprocal Teaching Method (RTM) boosts students' ability to comprehend the IELTS reading texts and engages them during the teaching and learning process.